Leading Across Generations: Configure Present-Day Leadership Style In Indonesia Soe Banking - Deniza Riski; Donald Crestofel Lantu (Eduvest - Journal of Universal Studies, 2025)
This study examines the leadership styles, leadership adaptability, and leaders perspective of developmental needs of a leading state-owned bank in Indonesia, BNI. This is taking place approximately one year after the bank was though its latest mass corporate transformation. With growing complexity, evolving roles, and increasing pressures for continuous transformation, these leaders must adeptly manage uncertainty, unify teams across several silos, and maintain unit performance under pressure. The study uses a method called qualitative descriptive phenomenology (Moustakas, 1994), that collects data from in-depth interviews, field notes and other previous related studies that thoroughly build the framework of the research. The findings show that leadership within the bank now is a blend of transformational and transactional, as leaders highly indicating participative, assertive and engaged actions, unconsciously avoiding any of Laissez-faire attitudes. There is, however, a prominent matter of how there is no structured support to help leaders learn to adapt. That implies leaders have to work on their own and adapt all the time. The study suggests on arranging a program: Leadership Adaptive Lab, a program that offers the chance to learn through doing challenging things, collaborating on projects with other teams, and a series of experiences to share and learn from. These are designed to create flexibility and establish a collective leadership identity within the company, while its aligns with the hopes from the BNI current leaders.